Relationship Between Homocysteine and Ischemic Stroke (Bangladesh Journal of Medicine, 2015)
Background: Epidemiologic studies have identified hyper-homocysteinemia as a possible risk factor for atherosclerosis. The aim of the study was based on evaluation of relationship between homocysteinemia with ischemic stroke patients.Methods and materials: It was a prospective observational study conducted in the Department of Neurology, Sir Salimullah Medical College & Mitford hospital, Dhaka. Thirty six consecutive patients with ischemic stroke were analyzed by serum total homocysteine, total cholesterol, HDLcholesterol, LDL-cholesterol, triglyceride and Equal number of of controls same ages were compared with the case group.Result: Mean Fasting blood sugar, serum fasting total cholesterol (TC), serum fasting Low density lipoprotein (LDL) were significantly higher in case group (p=0.001). Serum TC and LDL had a positive correlation with serum homocystine a (p=0.001). Serum High density lipoprotein (HDL) had a negative correlation (p=0.718) and serum triglyceride (TG) had a negative correlation (p = 0.182). Total plasma fasting homocysteine level in case group was 21.89 ± 9.38 ìmol/l and control group was 12.31 ± 3.27 ìmol/l, (p=0.001). Elevated fasting homocystein level was found in 75.0% of ischemic stroke patient and in 16.67% of healthy controls (p=0.001). The incidence of hyperhomocysteinemia is higher in ischaemic stroke cases than that in age-sex matched healthy controls. Hyperhomocysteinemia in ischaemic stroke patients has as been determined as vascular risk factor in our study. Significant correlation has been found between homocysteine concentration and ischaemic stroke.Bangladesh J Medicine Jan 2014; 25 (1) : 8-12